2016
DOI: 10.1002/cce2.36
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of the cardiac rhythm: where do we stand today?

Abstract: Remote monitoring systems, in their current forms, are networked communication solutions allowing exchange of digitized data from implanted or wearable devices. These data usually include electrocardiographic recordings, but nowadays they may encompass much more than that, allowing a continuously updated knowledge of a multitude of device‐ or patient‐related parameters. Remote monitoring has been shown, as one would have expected, to reduce the need for office visits and allow earlier detection—and thus manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The present landscape of ECG monitoring includes Holter monitors which allow up to 14 days of consecutive recording, external or implanted loop recorders and pacemakers or implanted defibrillators. 3 The patient experience with these devices vary, with issues such as poor long-term compliance, skin-related problems from external electrodes and low motivation particularly in the absence of frequent or recurrent symptoms hindering diagnostic yield. 4 Results from the CRYSTAL-AF and EMBRACE trials have demonstrated the value of longer periods of ECG monitoring in detecting new episodes of atrial fibrillation in patients with prior cryptogenic stroke or transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…The present landscape of ECG monitoring includes Holter monitors which allow up to 14 days of consecutive recording, external or implanted loop recorders and pacemakers or implanted defibrillators. 3 The patient experience with these devices vary, with issues such as poor long-term compliance, skin-related problems from external electrodes and low motivation particularly in the absence of frequent or recurrent symptoms hindering diagnostic yield. 4 Results from the CRYSTAL-AF and EMBRACE trials have demonstrated the value of longer periods of ECG monitoring in detecting new episodes of atrial fibrillation in patients with prior cryptogenic stroke or transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…Patients wear such a device for the desired period, then return the recorder box to the hospital, where the data are analyzed, and the results are reported to the patients. Other conventional tests include x-rays, echocardiography, or an electrophysiology study (Deftereos et al, 2016;Schweizerische Herzstiftung, 2022). If these examinations or short-term cardiac monitoring do not yield results, long-term von Arx .…”
Section: Introductionmentioning
confidence: 99%
“…Patients wear such a device for the desired period, then return the recorder box to the hospital, where the data are analyzed, and the results are reported to the patients. Other conventional tests include x-rays, echocardiography, or an electrophysiology study (Deftereos et al, 2016;Schweizerische Herzstiftung, 2022). If these examinations or short-term cardiac monitoring do not yield results, long-term Current cardiac monitors are barely the size of a triple-A battery, weigh about 4 grams, and are made of titanium, sapphire, parylene, silicone, or iridium components that protect the electronics and make them compatible with human tissue.…”
Section: Introductionmentioning
confidence: 99%